A comparison of fatty acid, cholesterol and vitamin composition in sea bass [Dicentrarchus labrax (Linnaeus, 1758)] and sea bream [Sparus aurata (Linnaeus, 1758)] from three cage farm areas: Antalya and Mugla (Turkey) and Iskele (Northern Cyprus) - Harlioglu, A. G.; Yilmaz, O.; Oray, I. K.; Aydin, S. (Wiley, 2016)
In the present study the fatty acids, cholesterol and vitamin composition in farmed sea bass (8 fish per species per farm; weight range: 389.6-395.8 g, total length range: 297-316 mm) and sea bream (8 fish per species per farm; weight range: 386.8-391.7 g, total length range: 263-268 mm) from three cage farms (Iskele in northern Cyprus, Antalya and Mugla in Turkey) were compared during the harvesting period in June-July 2011. The results showed that the muscles of D. labrax and S. aurata farmed fish were rich in n-3 fatty acids, but with important differences. For example, the muscles of sea bass farmed in Iskele were rich in docosahexaenoic acid (DHA) and n-3 polyunsaturated fatty acids (PUFA). Palmitic acid (C16:0) was the primary saturated fatty acid, and oleic acid (C18:1 n-9) the primary mono-unsaturated fatty acid in the muscle and liver samples of the cage-farmed sea bass and sea bream. There were no significant differences in the cholesterol content in the muscles of sea bream farmed in Iskele, Antalya or Mugla. In conclusion, the n-3/n-6 ratio in the muscle of farmed S. aurata and D. labrax is within the recommended limits for a healthy human diet, being very suitable for human nutrition.
1st International Fisheries Symposium -- MAR 24-27, 2013 -- Girne, CYPRUS
Keywords: Wild; Seabream; L.; Liver